(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Until now, the Republic of Uzbekistan has established innovative technologies for the health care of students, and one of its main goals and tasks is to educate our youth in a healthy way. In this article, information on methods based on innovative technologies for maintaining and strengthening the health of students is given. Also, students were given a number of instructions on the process of explaining healthy lifestyle and how to follow it. Also, in this article, it is explained that students should follow the rules of proper nutrition and not be indifferent to their health. One of the main goals and tasks of this article is to develop programs of innovative technologies for the health care of students.